2007
DOI: 10.1136/bmj.39308.392176.be
|View full text |Cite
|
Sign up to set email alerts
|

Patients' experiences of screening for type 2 diabetes: prospective qualitative study embedded in the ADDITION (Cambridge) randomised controlled trial

Abstract: Objectives To provide insight into factors that contribute to the anxiety reported in a quantitative study of the psychological effect of screening for type 2 diabetes. To explore expectations of and reactions to the screening experience of patients with positive, negative, and intermediate results.Design Prospective qualitative interview study of patients attending a screening programme for type 2 diabetes. Setting Seven general practices in the ADDITION (Cambridge) trial in the east of England. Participants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
66
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(75 citation statements)
references
References 17 publications
8
66
1
Order By: Relevance
“…A high-risk status was expressed as something already presumed but as yet non-imminent. A negative diagnosis and asymptomacy played a major role in scepticism concerning the risk, providing false reassurance, again as found in previous studies (Adriaanse et al, 2002;Eborall et al, 2007b). So far, qualitative studies have addressed false reassurance as a phenomenon decreasing one's risk perception.…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations
“…A high-risk status was expressed as something already presumed but as yet non-imminent. A negative diagnosis and asymptomacy played a major role in scepticism concerning the risk, providing false reassurance, again as found in previous studies (Adriaanse et al, 2002;Eborall et al, 2007b). So far, qualitative studies have addressed false reassurance as a phenomenon decreasing one's risk perception.…”
Section: Discussionmentioning
confidence: 70%
“…The expressions used indicated the difficulty of dealing emotionally with one's risk status; people were embarrassed by their risk status and they used social comparisons to gain an unrealistically positive view of their situation, increasing hope, and enhancing their self-esteem (Taylor & Lobel, 1989). They also made excuses to explain the risk away (see Eborall et al, 2007b). In addition, they downplayed the risk by taking it for granted, which may imply attempts to avoid negative emotions and to disengage with the risk (Carver & Connor-Smith, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Only a quarter of this group intended to have their blood glucose tested in future. Another study, which interviewed participants at different stages of a stepwise screening process (Eborall et al, 2007b), reported similar findings but noted that the stepped nature of the screening process appeared to help participants to adjust psychologically.…”
Section: The St Leonard's Practice Approach To Screening For Type 2 Dmentioning
confidence: 76%